2021
DOI: 10.1017/s1463423621000116
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to guideline recommendations for urinary tract infections in adult women: a cross-sectional study

Abstract: Aim: To study whether changes in drug preferences in the Dutch guideline for the treatment of Urinary Tract Infection (UTI) for General Practitioners (GPs) in 2013, resulted in corresponding changes in antibiotic dispensing. Background: For the treatment of uncomplicated UTI, nitrofurantoin remained the first choice, while fosfomycin became the second choice and changed ranks with trimethoprim. For a subsequent febrile UTI, ciprofloxacin became the first choice and changed ranks with amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Second, the Urologic Diseases in America study defined UTI by diagnostic coding plus the filling of an antibiotic prescription within 72 hours (and did not include the requirement for urine culture order in their inclusion criteria). Knowing that adherence to guidelines recommending urine culture before treatment in women with recurrent UTI is low, 8 our study may have underestimated those treated for possible UTI without a urine culture order. Conversely, the 30% number from the urologic disease project study could be overestimating the number of true UTIs.…”
Section: Discussionmentioning
confidence: 83%
“…Second, the Urologic Diseases in America study defined UTI by diagnostic coding plus the filling of an antibiotic prescription within 72 hours (and did not include the requirement for urine culture order in their inclusion criteria). Knowing that adherence to guidelines recommending urine culture before treatment in women with recurrent UTI is low, 8 our study may have underestimated those treated for possible UTI without a urine culture order. Conversely, the 30% number from the urologic disease project study could be overestimating the number of true UTIs.…”
Section: Discussionmentioning
confidence: 83%
“…In the Netherlands, 12–28% of E. coli strains isolated from urine in 2014 were resistant to trimethoprim [ 35 ]. In accordance with international guidelines, current Dutch guidelines around UTI care consequently recommended trimethoprim as the third drug of choice, behind nitrofurantoin and fosfomycin [ 36 , 37 ]. Therefore, while trimethoprim was a useful drug to promote at the time of the studies included in this review (and is definitely preferable to quinolones for the treatment of an uncomplicated UTI), any future interventions should focus on the use of any of the other antibiotics recommended by the guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic approach in this group focuses on prevention and self-management [ 2 ], with typical strategies including behavioral modification and both non-antimicrobial and antimicrobial prophylaxis [ 3 ]. A recent qualitative study among women with rUTI indicated marked variation in their knowledge of preventive measures [ 4 ].…”
Section: Introductionmentioning
confidence: 99%